2009
DOI: 10.1186/1472-6920-9-55
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in teaching improves learning in medical students: a randomized cross-over study

Abstract: Background: Peer-assisted learning has many purported benefits including preparing students as educators, improving communication skills and reducing faculty teaching burden. But comparatively little is known about the effects of teaching on learning outcomes of peer educators in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 22 publications
(23 reference statements)
1
79
0
5
Order By: Relevance
“…As previous research has shown, teaching others can be an effective way to enhance learning (e.g., Biswas et al, 2010;King et al, 1998;Palinscar & Brown, 1984;Peets et al, 2009;Roscoe & Chi, 2007) across a wide range of age groups including college (Annis, 1983), high school (Cloward, 1967;Morgan & Toy, 1970), middle school (Jacobson et al, 2001), and elementary school (Fuchs et al, 1996). That is, through learning by teaching, individuals theoretically learn content more deeply by teaching it to others compared with learning the content just for oneself.…”
Section: Learning By Teachingmentioning
confidence: 99%
See 3 more Smart Citations
“…As previous research has shown, teaching others can be an effective way to enhance learning (e.g., Biswas et al, 2010;King et al, 1998;Palinscar & Brown, 1984;Peets et al, 2009;Roscoe & Chi, 2007) across a wide range of age groups including college (Annis, 1983), high school (Cloward, 1967;Morgan & Toy, 1970), middle school (Jacobson et al, 2001), and elementary school (Fuchs et al, 1996). That is, through learning by teaching, individuals theoretically learn content more deeply by teaching it to others compared with learning the content just for oneself.…”
Section: Learning By Teachingmentioning
confidence: 99%
“…To date, the majority of previous research within the learning by teaching paradigm has focused on the effects of learning by teaching on learning outcomes (Biswas et al, 2010;Palinscar & Brown, 1984;Peets et al, 2009;Roscoe & Chi, 2007). Although some studies have explored whether learners organize and structure the content differently when learning by teaching, interpretations of these differences were based on learners' retrospective self-reports, on transfer tasks that required a better organizational structure of the content for greater performance, or on delayed performance tests (see Fiorella & Mayer, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence to suggest that teaching has a beneficial effect on the teachers, be they students themselves 7 or post-graduates 8 , as it improves confidence and often solidifies knowledge learned previously.…”
Section: Discussionmentioning
confidence: 99%